Mechanical and fluid transfer properties of some lime and Portland cement mortars. - PAVIA, SARA (Taylor and Francis Group, London., 2009)
The type of binder determines mortar properties, and these impact the durability of masonry. This paper intends to assist on the choice of mortar for a particular fabric, by investigating the properties of mortars made with calcium lime (CL90), Portland cement (PC) and natural hydraulic limes of three hydraulic strengths (NHL2, NHL 3.5, NHL5), and the influence of water content on mortar properties. The results evidenced an inverse relationship between the binder?s hydraulicity and the mortar?s shrinkage, porosity, capillary suction and water absorption; and a direct relationship between the binder?s hydraulicity and the mortar?s density and mechanical strength. The paper concludes that even though the volume of voids accessible to water in lime and cement mortars is comparable, the pore system of lime mortars is much more efficient transporting moisture by capillarity. It was noted that an increase in the mortar?s water content lowers bulk density, but does not significantly affect neither shrinkage nor the amount of voids accessible to water. It was also noted that, for the more hydraulic limes, mechanical strength tends to increase when mortars are mixed to higher flows, whereas feebly hydraulic mortars mixed to lower flow possess a superior mechanical resistance.
PUBLISHED
Keywords: mechanical properties, fluid transfer, lime mortars, PC mortars